PENGARUH SARANA PRASARANA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN SANTRI PONDOK PESANTREN MODERN SAHID BOGOR - Cahyani , Harti Nur; Rahmat , Imdadun; Chaniago , Asdi (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2024)
This study aims to determine the effect of infrastructure and service quality on the satisfaction of the students of Sahid Modern Islamic Boarding School Bogor in the 2021/2022 academic year partially and simultaneously. The method used is descriptive quantitative. The population in this study amounted to 736 students determining the sample with the Slovin formula so that the number of samples used in this study amounted to 88 students. Data collection techniques with questionnaires. The data analysis technique used in this study was multiple linear regression analysis. Analysis of the research instrument using the SPSS version 16.0 application. The results of the analysis consist of several tests, namely the validity test with Pearson Product Moment, all of which are declared valid. Reliability test with Cronbach's Alpha value > 0.6 and all the results are declared reliable. Normality test using the Kolmogorov-Smirnov (K-S) test and all the results were declared normal. Multicollinearity test using tolerance values and VIF and the results showed no symptoms of multicollinearity or intercorrelation. Heteroscedasticity test using the glejser test and the results showed no heteroscedasticity symptoms. The results of the statistical test of multiple linear regression analysis obtained regression Y=-5.485 + 0.072 X1 + 0.245X2. The t-test can be concluded: (a) The first hypothesis test (H1) is known that the sig value for the effect of X1 on Y is 0.149> 0.05 and the t-count value is 1.457 <1.98861, so it can be concluded that the H1 hypothesis is rejected, it means that the Infrastructure variable ( X1) does not affect student satisfaction (Y). (b) The second hypothesis test (H2) is known that the sig value for the effect of X2 on Y is 0.00 <0.05 and the t value is 10.164 > 1.98861, so it can be concluded that the H2 hypothesis is accepted, it means that the service quality variable (X2) affects Student Satisfaction (Y). The results of the statistical test f can be concluded: the significance value for the influence of Infrastructure (X1) and Service Quality (X2) on Student Satisfaction (Y) is 0.00 < 0.05 and the calculated F value is 124.286 > 3.10 so it can be concluded that H3 accepted, which means there is a simultaneous influence (X1) Infrastructure and (X2) service quality on (Y) student satisfaction. In the results of the coefficient of determination, the value of the Adjusted R Square is 0.739. It can be concluded that the Independent Variable (X) affects the Dependent Variable (Y) by 73.9% Islamic religious tertiary institutions are expected to produce graduates who are qualified and have an entrepreneurial spirit who are able to create jobs. Likewise, an Islamic educational institution, in this case the Private Islamic Religious College (PTKIS), especially the Bogor Sahid Islamic Institute (INAIS), must continue to strive to improve quality in an effort to maintain its existence and survive amidst the very tight competition in the world of education today. . To achieve these ideal conditions, higher education institutions in general and in this case INAIS must clearly have a vision and mission that are in line with today's, tomorrow's and future needs. The purpose of this study is to analyze the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University. The type of research used is qualitative research with a descriptive analytical case study approach and library research. The results in the study show that the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University has not been fully achieved because there are obstacles faced by the Sahid Islamic Institute, one of which is because there are many graduate or alumni professions who are not entrepreneurs so that a strategy is needed, namely to improve education. and teaching, research and community service as well as supported by infrastructure that supports the achievement of entrepreneurial competence.